1993
DOI: 10.1093/jn/123.7.1217
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the Hypothalamic-Pituitary-Adrenal Axis is Elevated in Rats with Activity-Based Anorexia

Abstract: Activity-based anorexia is characterized by suppressed food intake and excessive physical activity. These behaviors are typical of persons with anorexia nervosa. Activity of the hypothalamic-pituitary-adrenal axis is known to be elevated in anorexia nervosa. We investigated the status of this axis in activity-based anorexia. Meal fed-control (MFC) and meal fed-wheel running (MFWR) rats were given access to food for 90 min daily; MFWR animals were allowed access to an activity wheel the remainder of the day. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…It has been reported that olanzapine treatment enhances ingestive behavior in food-deprived rats (Thornton-Jones et al 2002); however, it is possible that the 1-hour feeding period in our experiment was too short to observe an orexigenic effect of olanzapine. As a result of restricted feeding and wheel running, the HPA axis is considerably activated in ABA rats (Burden et al 1993). In our study, it was shown that olanzapine treatment decreased ACTH levels and tended to decrease corticosterone levels and adrenal weight in ABA rats, thereby reducing stress levels in ABA rats.…”
Section: Discussionsupporting
confidence: 47%
“…It has been reported that olanzapine treatment enhances ingestive behavior in food-deprived rats (Thornton-Jones et al 2002); however, it is possible that the 1-hour feeding period in our experiment was too short to observe an orexigenic effect of olanzapine. As a result of restricted feeding and wheel running, the HPA axis is considerably activated in ABA rats (Burden et al 1993). In our study, it was shown that olanzapine treatment decreased ACTH levels and tended to decrease corticosterone levels and adrenal weight in ABA rats, thereby reducing stress levels in ABA rats.…”
Section: Discussionsupporting
confidence: 47%
“…Previous studies reported that the effects of resocialization, like decreased food intake and body weight, were attributed to various factors like housing changeinduced temporary stress, 12 mutual hindrance in feeding, 11 increased bodily activity and energy expenditure. 53,54 We, therefore, suggest that, re-socialization might reverse the effects of isolation including the chronic psychological stress. The effects of re-socialization were also reflected in the CART immunohistochemistry profile.…”
Section: Discussionmentioning
confidence: 90%
“…Enhanced RWA is specifically observed a few hours prior to food access, a phenomenon, which is described as food-anticipatory activity (FAA) (Mistlberger, 1994). Additionally, rats decrease food intake, lose body weight as well as body temperature and the hypothalamus-pituitary-adrenal (HPA) axis is activated (Burden et al, 1993;Hall and Hanford, 1954;Hillebrand et al, 2005a;Routtenberg and Kuznesof, 1967).…”
Section: Introductionmentioning
confidence: 99%